THE DESCRIPTION NAMING OF SUB-VILLAGE AND CULTURAL VOCABULARY DIVERSITY AT BAWODESOLO VILLAGE - Zendrato, Nicky Elvin Cristin; Telaumbanua, Nita Trima Niat; Waruwu, Mewi Dinda Arcila; Lawolo, Arni Yanti; Harefa, Afore Tahir (Universitas Muhammadiyah Lampung, 2024)
This research aims to describe the naming of sub-villages and the diversity of cultural vocabulary in Bawodesolo Village, Gunungsitoli District, Gunungsitoli City, North Sumatra Province. The focus of this research is on three sub-villages: Delafiga, Hilinangea, and Simanaere. Using a phenomenological research design, this study involves semi-structured interviews with local residents to understand the meanings and cultural contexts of these sub-village names. The results of the research show that the sub-village names reflect the cultural identity, history, and values of the local community. Names such as